Pudukkottai State, Report - Dandapani Ayyar, Rao Sahib. S. (Karnataka, 1931)
Distribution and movement of the population, Villages and towns, Birthplace, Age, sex civil condition, Infirmities, Occupation, Literacy, Languages, Religion, Race, tribe or caste.
Keywords: Pudukkottai State; Report